Dinamika Pendidikan Islam Terpadu (Studi Kasus Di Yayasan Muhammad Yaqub Bulurejo Diwek Jombang) - Khumairoh An-Nahdliyah (Al Hikmah: Jurnal Studi Keislaman, 2018)
Abstract: At least there are two trends that can be identified with regard to the age ofglobalization. First, the stronger dominance of science and technology in science inhuman life. Second, the strong dominance of science and technology slowly shifts thenoble values that are universally upheld by humans. Educational institutions inIndonesia, on average, mostly teach general lessons and are less able to form Islamicpersonalities for students or Muslim personalities, therefore an Islamic personalitythat is oriented towards the welfare and happiness of life in the world and thehereafter is needed. The integrated Islamic education model implemented at theMuhammad Yaqub Foundation is an integration model, using an interdisciplinaryapproach, combining the fields of study of skills, overlapping concepts and attitudes.Like learning about physics, but students have skills about faith. this curriculumincludes integrating several disciplines. The development of integrated IslamicEducation at the Muhammad Yaqub Foundation is to structure the curriculum,syllabus, textbooks, teaching staff, develop a teacher team that will provide anexplanation of faith and piety, conduct teacher coaching, lecture students who will beexpected to graduate as teachers in Muhammad Yaqub Foundation to be fostered. Keywords: Integrated Islamic Education, integration model and Muhammad YaqubFoundation